PERANAN INTERNAL AUDITOR DALAM PENDETEKSIAN DAN PENCEGAHAN KECURANGAN - ., SOEHARMORO (Berkala Ilmiah Mahasiswa Akuntansi)
The successful completion of the audit engagement is determined by the quality of the audit plan prepared by the auditor. This suggests that the lower the risk of corporate governance faced by auditors, the audit planning requires a long time and conversely, the higher the risk of corporate governance faced by auditors, the audit plan does not require a long time. Alternatively, effective corporate governance mechanisms or whether the client is not a risk to the auditor in considering when planning the audit. Low risk of earnings management, corporate governance related to audit planning. Corporate governance will be able to reduce earnings management undertaken by the company management. In addition, the system of good corporate governance can provide effective protection to shareholders and creditors.